Healthy Cardiovascular Status Attenuates the Detrimental Association Between Osteosarcopenic Adiposity and Alzheimer's Disease‐Related Dementia: A UK Biobank Cohort Study - Wenxu Wang; Rui Ren; Honghao Yang; Jinguo Jiang; Xingyue Ye; Chenying Wang; Xiang Ji; Wen Li; Yuhong Zhao; Yang Xia; Difei Wang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Body composition abnormalities are associated with the risk of Alzheimer's disease‐related dementia (ADRD). However, the specific link between osteosarcopenic adiposity (OSA), cardiovascular health (CVH), and ADRD is underexplored. This study examined the association between OSA and ADRD to determine whether optimal CVH could modify this association. Methods We analyzed data from 152 028 UK Biobank participants. OSA‐related body composition abnormalities include low bone mineral density, low muscle mass/grip strength, and high body fat percentage. CVH was assessed using the Life's Essential 8 questionnaire. High and low CVH corresponded to the lowest and highest cardiovascular disease risks, respectively. The hazard ratios (HRs) and 95% CIs for ADRD were estimated using Cox proportional hazards models. A secondary analysis included 14 750 participants with brain magnetic resonance imaging data to explore the role of brain structure in the association between OSA and the incidence of ADRD. Results After a median follow‐up of 14.1 years, 2628 participants (1.73%) developed ADRD. Compared with participants with no body composition abnormalities, the adjusted HRs for ADRD risk for those with 1, 2, and 3 abnormalities were 1.04 (95% CI, 0.95–1.14), 1.17 (95% CI, 1.04–1.31), and 1.46 (95% CI, 1.11–1.92), respectively. We found a significant addictive interaction between CVH and abnormal body components, with a relative excess risk due to interaction (95% CI) of −1.34 (95% CI, −2.11 to −0.57). Gray matter in the hippocampus could mediate these associations, with a mediation proportion of 17.3% (P < 0.001). Conclusions OSA components are positively associated with the risk of ADRD. Maintaining optimal CVH status may mitigate ADRD risk in individuals with OSA.